2016
DOI: 10.3389/fgene.2016.00219
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping-by-Sequencing Uncovers the Introgression Alien Segments Associated with Sclerotinia Basal Stalk Rot Resistance from Wild Species—I. Helianthus argophyllus and H. petiolaris

Abstract: Basal stalk rot (BSR), caused by Sclerotinia sclerotiorum, is a devastating disease in sunflower worldwide. The progress of breeding for Sclerotinia BSR resistance has been hampered due to the lack of effective sources of resistance for cultivated sunflower. Our objective was to transfer BSR resistance from wild annual Helianthus species into cultivated sunflower and identify the introgressed alien segments associated with BSR resistance using a genotyping-by-sequencing (GBS) approach. The initial crosses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Many of USDA's activities are continuation of previous uses of CWR, mostly centred on diversification of sources of resistance to disease. Introgressions from H. praecox, H. argophyllus, and H. petiolaris have been associated with Sclerotinia basal stalk rot resistance (Qi et al, 2016;Talukderet al, 2019) and were combined with downy mildew (caused by Plasmopara halstedii) resistance previously recovered from the primary CWR (Hulke et al, 2010). Similar work in diversification of downy mildew resistance sources has come from the secondary CWR pool, as well, with the independent genes Pl18, Pl20, and Pl35 recently introgressed from H. argophyllus (Qi et al, 2019).…”
Section: Use Of Cultivated Sunflower and Cwr Resources In Breedingmentioning
confidence: 99%
“…Many of USDA's activities are continuation of previous uses of CWR, mostly centred on diversification of sources of resistance to disease. Introgressions from H. praecox, H. argophyllus, and H. petiolaris have been associated with Sclerotinia basal stalk rot resistance (Qi et al, 2016;Talukderet al, 2019) and were combined with downy mildew (caused by Plasmopara halstedii) resistance previously recovered from the primary CWR (Hulke et al, 2010). Similar work in diversification of downy mildew resistance sources has come from the secondary CWR pool, as well, with the independent genes Pl18, Pl20, and Pl35 recently introgressed from H. argophyllus (Qi et al, 2019).…”
Section: Use Of Cultivated Sunflower and Cwr Resources In Breedingmentioning
confidence: 99%
“…Quantitative trait loci (QTL) mapping of partial BSR resistance in the cultivated sunflower indicated that the resistance is controlled by multi‐genes with additive effects (Davar et al, 2010; Amouzadeh et al, 2013; Talukder et al, 2016). This was also the case for the wild species where introgressed alien segments were detected in several chromosomes in the BSR‐resistant lines revealed by genotyping‐by‐sequencing (Qi et al, 2016b).…”
mentioning
confidence: 67%
“…Sclerotinia BSR evaluations of the early generations of F 1 through BC 2 F 2 were performed in the greenhouse under controlled conditions during winter and early spring as described by Qi et al (2016b). In the BC 2 F 2 generation, 11 BSR‐resistant BC 2 F 3 families were selected from 768 BC 2 F 2 plants of the cross NMSHA 89/ H. petiolaris PI 435843, and 20 BSR resistant BC 2 F 3 families were selected from 644 BC 2 F 2 plants of the cross NMSHA 89/ H. argophyllus PI 494573 from greenhouse tests in winter 2011.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative transgenic methods have been developed to reinforce sunfl ower resistance to diseases. A number of homologues resistance (R) gene have been isolated from sunfl ower, providing a valuable resource for engineering disease resistance in sunfl ower (Dimitrijevic and Horn 2018;Hewezi et al, 2006;Qi et al, 2016;Talukder et al, 2016).…”
Section: Resistance To Pathogensmentioning
confidence: 99%